EXPRESSION OF MORAL VALUES IN ORATORY ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
This thesis examines the expression of moral values in oratory as an important aspect of speech culture, public communication and ethical education. Oratory is not only the art of speaking beautifully and persuasively, but also the ability to express ideas responsibly, honestly and respectfully. Moral values such as truthfulness, justice, respect, responsibility, human dignity, patriotism, tolerance and social duty are reflected in the content, tone, argumentation and purpose of public speech. The study shows that a speaker’s influence depends not only on linguistic skill but also on ethical position. The thesis analyzes the concept of moral values in oratory, their structural expression, educational importance, practical application and current problems in modern public speaking.